Development of Acid Base e-learning (e-PAB) Module using Google Classroom: Pembangunan Modul e-pembelajaran Asid Bes (e-PAB) Menggunakan Google Classroom - Rahim, Norfariana; Lee, Tien Tien (Journal of Science and Mathematics Letters, 2021)
This study aims to develop an Acid Base e-Learning module (e-PAB) using Google Classroom. This study also identified the validity, realibility and trainee teachers’ perception on content, design and usability of the module. This is a design and development research. The ADDIE model is used as the instructional design model in developing e-PAB module. Three instruments were used in this study: content validity evaluation form, module reliability questionnaire and the module perception questionnaire. Three chemistry lecturers have been appointed to assess the content validity of the module. A total of 32 form four students have been used as sample in studying the reliability of the module. A total of 175 trainee teachers from the Bachelor of Chemistry Education programme have been selected as respondents for the field study. The findings show that the validity coeficient is 0.85 and the value of the reliability coefficient is 0.87. The field study’s data were analyzed using descriptive statistics. The findings show that perception of trainee teachers on the content of the module gains a mean score of 3.71 (SD= 0.45), the mean score for the design of the module is 3.71 (SD = 0.46) and the usability of the module is 3.74 (SD = 0.44). In conclusion, e-PAB module has a high content validity and reliability value. Trainee teachers' perception of the module also has a high mean value. Implication of the study is e-PAB module is suitable as a reference and online learning material for the acid base topic.